Functions of coastal feeder bluff systems: Implications for prioritizing protection and restoration - Jason D. Toft; Julia N. Kobelt; Kerry L. Accola; Megan N. Dethier; Andrea S. Ogston; Sarah E. Vollero (PLoS ONE, 2025)
Actively eroding cliffs, known as feeder bluffs, are important sources of sediment for coastal beaches. When shorelines have artificial armor, natural beach sediment processes can be disrupted. A recent management tool in the Salish Sea, WA, USA prioritizes efforts with high potential benefit of restoration (armor removal) or protection (preventing armor construction) to nearshore sediment supply. We conducted field sampling at 20 beaches identified as the highest or lowest priorities for restoration or protection, so we could examine local ecological and physical functions, in addition to potential landscape benefits. We sampled parameters spanning the top of the bluff to the low shore, and evaluated a total of 30 metrics including riparian vegetation, invertebrate assemblages, logs, beach wrack, fish abundance and behavior, surface epifauna and algae, beach and bluff characteristics, and sediment size and sorting. For analyses, we calculated an average score of beach function for each of four treatments: “Protect High” (unarmored, ranked as high management priority), “Protect Low” (unarmored, ranked low), “Restore High” (armored, ranked high), and “Restore Low” (armored, ranked low). Protect High and Low treatments were equivalent in local beach function, and both scored over twice as high as Restore treatments. Restore High scored only slightly higher than Restore Low, indicating a consistent degradation caused by armoring on bluffs with variable sediment source potential. Statistical models revealed that overall beach function may be largely driven by upper beach metrics including wrack, logs, and overhanging vegetation. Metrics for geomorphology and lower beach organisms were more variable, likely due to differences in geographical region and distance from the bluff. Our results indicate that beaches with natural unarmored bluffs have the highest level of localized ecological function regardless of the level of potential sediment supply, and restoring sediment supply processes at beaches with armored bluffs could double their ecological function.